Densification of non-radioactive porous siliceous particles loaded with cesium potassium copper hexacyanoferrate by spark plasma sintering. Issue 2 (February 2021) - Massoni, Nicolas; Le Gallet, Sophie; Campayo, Lionel; Koch, Robert J.; Misture, Scott T.; Grandjean, Agnès; Bernard, Frédéric
Abstract: In the development of a conditioning process for cesium-bearing sorbents from the decontamination of aqueous waste streams, the treatment of a granular material composed of (Cs, K)2 CuFe(CN)6 loaded onto mesoporous silica particles has been investigated in an additive-free two-step conditioning process involving (i) calcination at 1000 °C to remove volatile species and (ii) densification by spark plasma sintering. A 92.0 % dense pellet was obtained after 10 min sintering at 850 °C under 100 MPa. Density and microstructural measurements indicate that densification is first driven by the viscous flow of a vitreous phase containing Cs, formed during calcination. The density of the sample then increases further during sintering by grain boundary diffusion. However, a limited but non negligible part of cesium is lost during densification.